Adopsi Komoditas Adaptif Lahan Gambut: Faktor Penentu, Dampak Pendapatan, dan Keterkaitan dengan Restorasi di Kabupaten Banjar, Kalimantan Selatan - Adam Maulana; Maulida Murdayanti; Sarbaini; Ria Anita Pertiwi (Jurnal Sosial Ekonomi Pertanian, 2026)
This study aims to analyze the factors influencing the adoption of peatland-adaptive commodities, their impact on farmers' income, and their relationship with peatland restoration program support in Banjar Regency, South Kalimantan. An analytical observational cross-sectional design was employed with 100 farmer respondents (49 Adapters and 51 non-Adapters) selected through purposive random sampling in Gambut and Aluh-Aluh Districts from April to August 2025. Data were analyzed using Spearman correlation, Mann-Whitney U, Chi-Square, Pearson correlation, and forward stepwise logistic regression. The results indicate that price fluctuation is the only significant factor influencing adoption (OR=1.999; p=0.008). Livestock Adapters had significantly higher income of IDR 30.0 million (113.7%) compared to non-Adapters (p=0.023), while horticultural Adapters showed no significant difference (p=0.614). Adoption status did not correlate with restoration attitudes (r=0.036; p=0.719) or restoration program participation (r=0.029; p=0.776), although a strong positive correlation was found between restoration attitudes and participation (r=0.586; p<0.001). Peatland-adaptive commodity adoption in Banjar Regency is primarily driven by economic risk-mitigation motives, produces heterogeneous income impacts depending on commodity type, and remains institutionally disconnected from formal peatland restoration programs. Integrated policy incentives explicitly linking adaptive commodity adoption with restoration objectives are urgently needed